Role of urinary nephrin to predict early onset of nephropathy in patients with type 2 diabetes mellitus (Panacea Journal of Medical Sciences, 2024)
Background: Nephropathy is most common complication in type 2 diabeticsubjects. Urinary nephrin is a podocyte specific protein, can be serve as a predict early nephropathy and its progression of diabetic nephropathy.Materials and Methods: A total 90 participants included were sub grouped as 60 cases and 30 healthy controls, a biochemical, clinical and experimental parameters were analyzed for all the study subjects. The data was interpreted by using statistics software SPSS and  Results: There were significantly increased levels of FBS, PPBS and glycated haemoglobin in type 2 diabetic cases when compared to controls. The urea, creatinine, uric acid and microalbumin were significantly elevated in type 2 diabetic with microalbuminuria when compared to type 2 diabetic with normoalbuminuria and controls. Additionally the urinary nephrin was significantly elevated in both groups of type 2 diabetics when compared to controls.Conclusion: This study suggests determination of urinary nephrin can be used as an early predictable and prognostic marker for nephropathy in patients with type 2 diabetics